Leveraging intellectual capital dimensions for promoting learning organization in a rural development agency - Ramli, Amiruzie; Mohd Rasdi, Roziah (Universiti Putra Malaysia Press, 2021)
Given the considerable intangible resources within organizations in the public sector must be put to good use, e.g. to enhance organizational learning. This study examined three intellectual dimensions of intellectual capital (human, structural, and relational) in a rural development organization and their contributions to a learning organization. Using simple random sampling, research data were obtained from 153 managers, including Heads of Department at the Headquarters and at Regional and Settlement Offices covering Peninsular Malaysia’s Northern, Southern, Central, and Eastern regions. Pearson Product Moment Correlation Coefficient and Multiple Linear Regression were carried out and the results supported the hypotheses that the dimensions of intellectual capital, namely human, structural and relational capital, were positively correlated with the learning organization, with structural capital being the most significant predictor.